Teriflunomide for the Treatment of Multiple Sclerosis - Oh, Jiwon; O'Connor, Paul W. (Seminars in Neurology, 2013)
Several novel oral agents are emerging for use in multiple sclerosis (MS). Among these oral agents, teriflunomide is showing promise with respect to clinical efficacy and safety in relapsing MS patients. In this review, the authors clarify the role of teriflunomide in the context of current and emerging MS treatment options by summarizing salient points on the use of teriflunomide in MS, with a discussion of teriflunomide's development, pharmacologic properties, preclinical and clinical trials, and safety and tolerability.
Keywords: teriflunomide; multiple sclerosis; clinical trials